Cultural ecosystem values of the Kimberley coastline: An empirical analysis with implications for coastal and marine policy. (1st August 2018) - Kobryn, Halina T.; Brown, Greg; Munro, Jennifer; Moore, Susan A.
Abstract: Cultural ecosystem services have received increasing attention in land/marine use planning but remain poorly known, expressed, and utilised in planning processes. Progress in marine spatial planning requires better information regarding the full range of values and benefits received from ecosystem services, including cultural ecosystem values. This paper reports on an online Public Participation GIS (PPGIS) study that collected spatially explicit information on cultural ecosystem values in the remote Kimberley coastal region in northwestern Australia. The coastal zone – 20 km landwards and seawards – was found to be highly valued with values disproportionally located 0–2 km onshore. The number of value markers placed was related to tenure, access (i.e., density of tracks), population density, and geomorphology. Methodologically, Public Participation GIS describes the location and extent of values providing for the exploration of relationships between values and other planning features such as tenure and coastal access. Inclusion of such information in marine spatial planning and policy formulation can contribute to more thoughtful and inclusive decisions regarding the future of coastal zones. The use of internet-based Public Participation GIS is particularly useful for long, remote coastlines with widely dispersed stakeholder interests where other methods such as interviews and workshops are not feasible. Highlights: Cultural ecosystem services have received little attention in marine or land use planning. Online PPGIS social values data were collected to fill the knowledge gap in northwest Australia. PPGIS methodology allowed for explicit exploration of values and planning features. Remote coastlines with dispersed stakeholders lend themselves to the PPGIS methodology.